Qualitative Phytochemical Screening and In Vitro Evaluation of Antibacterial Activities of Curcuma longa Linn. Leaf and Rhizome Essential Oils - Ferrer, Daryl Markovnikov Talabero
The increasing incidence of multi-drug resistant bacteria and infectious diseases lead the researchers to find and develop new antibacterial compounds. Curcuma longa or turmeric is widely used as a spice and coloring agent, and as well known for its medicinal properties. This study aimed to evaluate the antibacterial activities of turmeric leaf and rhizome essential oils through Kirby-Bauer disc diffusion and determine the phytochemicals present through qualitative screening. One-way analysis of variance was used a statistical tool and further evaluated by using Duncan?s Multiple Range Test. The leaf and rhizome essential oils of C. longa can inhibit the growth of Bacillus cereus, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. .Rhizome oil is more effective on Gram-positive bacteria. Both Gram-positive bacteria already showed resistance to 500μg/μl concentration of leaf and rhizome oil thus, 1000μg/μl concentration will be considered as the minimum inhibitory concentration (MIC) of both oils to B. cereus and S. aureus. Rhizome oil at 500μg/μl concentration is the MIC to E.coli and P. aeruginosa. The concentration of leaf oil at 1000μg/μl as its MIC to E.coli and the leaf oil at 250μg/μl concentration is the MIC to P. aeruginosa. Alkaloids, saponins and terpenoids were found in both oils. The probable mechanisms of action of the essential oils on bacteria are given by their hydrophobic and lipophilic nature. The phytochemical constituents present in turmeric leaf and rhizome oils are responsible can be attributed for its antibacterial activity.